1992
DOI: 10.1111/1540-5850.00939
|View full text |Cite
|
Sign up to set email alerts
|

Virginia's Revenue Forecasting Process and Models

Abstract: In Virginia, major differences between revenue forecasts and actual revenue collections raised questions from legislators about the adequacy of the state's econometric forecasting models and the forecasting process itself. Consequently, Virginia's process and models were examined by the Joint Legislative Audit and Review Commission (JLARC), a legislative watchdog agency. The review found most of the differences could be attributed to declining economic factors and not poor forecasting. However, a surprisingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Shkurti and Winefordner () describe an instance in Ohio in the late 1980s in which the competing political parties produced their own forecast estimates and accused one another of producing manipulated numbers that served their own political interests. Jonas, Rest, and Atkinson () find that forecast errors in Virginia were more attributable to economic factors than poor forecasting, although much of the forecast was based on undocumented judgmental inputs. Krause and Douglas () find that forecast error carries a quadratic effect with respect to political diversity on the consensus forecasting panel, suggesting that there can be both too much or too little comprehensive political inclusion involved with forecast accuracy.…”
Section: Previous Literature: Revenue Forecast Methods and Errorsmentioning
confidence: 99%
“…Shkurti and Winefordner () describe an instance in Ohio in the late 1980s in which the competing political parties produced their own forecast estimates and accused one another of producing manipulated numbers that served their own political interests. Jonas, Rest, and Atkinson () find that forecast errors in Virginia were more attributable to economic factors than poor forecasting, although much of the forecast was based on undocumented judgmental inputs. Krause and Douglas () find that forecast error carries a quadratic effect with respect to political diversity on the consensus forecasting panel, suggesting that there can be both too much or too little comprehensive political inclusion involved with forecast accuracy.…”
Section: Previous Literature: Revenue Forecast Methods and Errorsmentioning
confidence: 99%
“…After studying revenue forecast error in the State of Virginia, Jonas, Rest, and Atkinson (1992) reported the findings of a Joint Legislative Review and Audit Commission (JLARC) that was created to investigate the source of forecast error in the state. JLARC found that most of the forecast error in Virginia was a result of declining economic conditions rather than poor forecasting.…”
Section: Bias In State Revenue Forecastingmentioning
confidence: 99%
“…Concerning forecast accuracy in particular, studies found when there were independent forecasts by competing agencies in a state, forecast accuracy increased (Bretschneider & Gorr, 1987;Bretschneider et al, 1989). Other studies that lent support to the desirable attributes of consensus forecasting include the study of Virginia's forecasting experience by Jonas et al (1992) and the study of revenue forecasting in Michigan by Hass and Knittel (1998). Some studies, however, were not consistent with the positive relationship between forecast accuracy and the use of outside advisors or consultants, and between forecast accuracy and competitive forecasts (Forrester, 1993;Mocan & Azad, 1995;Schroeder, 1982).…”
Section: External Political Influencesmentioning
confidence: 99%
“…A number of studies have emphasized the importance of quality information in forecasts, which relies on cooperation among all the agencies involved. For instance, Jonas et al (1992) found Virginia's state revenue forecasting process and forecast accuracy could be improved by providing more timely information and sharing the information more consistently between the executive branch, the legislature, and the public. Over-dependence on information from outside sources, on the other hand, was found to be detrimental to state budget officials' learning (Klay, 1985).…”
Section: The Role Of Information In Forecastingmentioning
confidence: 99%
See 1 more Smart Citation